Have Synergies Between Nitrogen Deposition and Atmospheric CO2 Driven the Recent Enhancement of the Terrestrial Carbon Sink?. Issue 2 (10th February 2019) - O'Sullivan, Michael; Spracklen, Dominick V.; Batterman, Sarah A.; Arnold, Steve R.; Gloor, Manuel; Buermann, Wolfgang
Abstract: The terrestrial carbon sink has increased since the turn of this century at a time of increased fossil fuel burning, yet the mechanisms enhancing this sink are not fully understood. Here we assess the hypothesis that regional increases in nitrogen deposition since the early 2000s has alleviated nitrogen limitation and worked in tandem with enhanced CO2 fertilization to increase ecosystem productivity and carbon sequestration, providing a causal link between the parallel increases in emissions and the global land carbon sink. We use the Community Land Model (CLM4.5‐BGC) to estimate the influence of changes in atmospheric CO2, nitrogen deposition, climate, and their interactions to changes in net primary production and net biome production. We focus on two periods, 1901–2016 and 1990–2016, to estimate changes in land carbon fluxes relative to historical and contemporary baselines, respectively. We find that over the historical period, nitrogen deposition (14%) and carbon‐nitrogen synergy (14%) were significant contributors to the current terrestrial carbon sink, suggesting that long‐term increases in nitrogen deposition led to a substantial increase in CO2 fertilization. However, relative to the contemporary baseline, changes in nitrogen deposition and carbon‐nitrogen synergy had no substantial contribution to the 21st century increase in global carbon uptake. Nonetheless, we find that increased nitrogen deposition in East Asia since the early 1990s contributed 50% to the overall increase in net biome production over this region, highlighting the importance of carbon‐nitrogen interactions. Therefore, potential large‐scale changes in nitrogen deposition could have a significant impact on terrestrial carbon cycling and future climate. Key Points: Increased CO2 concentrations and nitrogen deposition combined synergistically to increase the land carbon sink over the 20th century Carbon‐nitrogen synergies do not appear responsible for the increase in land carbon sink since the beginning of the 21st century